Ectopic pregnancy in a tertiary care center: a retrospective study - Shivananjaiah, Chaitra; U., Ashwini Nayak; Swaminathan, Kamya Ramesh; Swarup, Asha; Pocha, Suneha; Pathadan, Davis Sabu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Ectopic pregnancy is an obstetric emergency which if not diagnosed in time can cost the life of the patient. This emphasizes the importance of diagnosing this perilous condition and hence this study was undertaken to study symptoms with which the patients with ectopic pregnancy present. Methods: Retrospective study of 5 years was done in the department of Obstetrics and Gynecology, M. S. Ramaiah medical college and teaching hospital, Bangalore, India between January 2011 to January 2016. Detailed analysis of patients with ectopic pregnancy inclusive of the age and clinical features were studied. Results: A total of 90 patients with ectopic pregnancy were studied. 95.5% of the patients (n=86) presented with abdominal pain, 81.1% (n=73) of the patients presented with amenorrhea, 24.4% (n=22) patients presented with bleeding per vagina, 30% (n=27) patients with nausea, vomiting and 48.8% (n=44) presented with fainting and giddiness. Conclusions: It is very essential to study the symptoms of ectopic pregnancy as this may help in early detection of ectopic pregnancy and hence can reduce the mortality in this catastrophic condition.